MEDIA MANIPULATIF DARI KERTAS DALAM PEMBELAJARAN OPERASI HITUNG PECAHAN - Suparni Suparni (IAIN Padangsidimpuan, 2015)
AbstractStudents study Fractions for main mathematics subject in elementary school. The study is about calculation, subtraction, multiplication and division for ordinary fractions, unordinary fraction and decimal.Finally, the centre of curriculum and education affair, research and development department says that fraction is a difficult subject to teach.It is due to teacher’s meaningless study and unsupported study media for right subject.Key words: fake media, paper, fraction calculation operation